2019
DOI: 10.1266/ggs.18-00062
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MCM2–7 proteins at senescence

Abstract: Cellular aging is characterized by the loss of DNA replication capability and is mainly brought about by various changes in chromatin structure. Here, we examined changes in MCM2-7 proteins, which act as a replicative DNA helicase, during aging of human WI38 fibroblasts at the single-cell level. We used nuclear accumulation of p21 as a marker of senescent cells, and examined changes in MCM2-7 by western blot analysis. First, we found that senescent cells are enriched for cells with a DNA content higher than 4N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It belongs to MADS box transcription factor family ( Pramila et al, 2002 ). The MCM2-7 form a heterohexameric complex that serves as a DNA duplicating helicase, which unwinds the DNA duplex template during DNA replication ( Fei and Xu, 2018 ; Suzuki et al, 2019 ). MCM8 and nine were reported to make up the CMG complex with Cdt1 and GINS.…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to MADS box transcription factor family ( Pramila et al, 2002 ). The MCM2-7 form a heterohexameric complex that serves as a DNA duplicating helicase, which unwinds the DNA duplex template during DNA replication ( Fei and Xu, 2018 ; Suzuki et al, 2019 ). MCM8 and nine were reported to make up the CMG complex with Cdt1 and GINS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the levels of MCM2-7 proteins were reported to decrease in replicative senescence (Suzuki et al, 2019). Notably, in both studies, MCM7 translocated to the cytosol with either increasing age or senescence, suggesting that besides steady-state levels, the exit from the nucleus could represent a full loss-of-function for MCM7.…”
Section: Pathways Less Active In Primary Skin Fibroblasts From Older ...mentioning
confidence: 73%
“…It was previously reported that the levels of MCM2‐7 proteins were significantly lower in HDFs derived from healthy aged donors, and a role for MCM7 in proliferation was established by selective knockdown approaches (Dumit et al., 2014 ). Similarly, the levels of MCM2‐7 proteins were reported to decrease in replicative senescence (Suzuki et al., 2019 ). Notably, in both studies, MCM7 translocated to the cytosol with either increasing age or senescence, suggesting that besides steady‐state levels, the exit from the nucleus could represent a full loss‐of‐function for MCM7.…”
Section: Discussionmentioning
confidence: 89%
“…There is evidence that transcription of mcm (for minichromosome maintenance) genes increases during the G1 phase of cell cycle. It is also known that limited levels of MCM proteins may disrupt cell proliferation through the arrest of cell cycle progression at G1 phase and may be associated to the status of cell senescence 29 , 30 . A decrease of cell proliferation process in the haemal tissue sampled in the recovered group (s-L/rec) is supported by the down expression of pcna gene ( p = 0.019) (supplementary data 1 ).…”
Section: Discussionmentioning
confidence: 99%